Existing global marine protected area network is not representative or comprehensive measured against seafloor geomorphic features and benthic habitats. (1st January 2019) - Fischer, Andrew; Bhakta, Debhasish; Macmillan-Lawler, Miles; Harris, Peter
Abstract: The Aichi targets of the Convention on Biological Diversity leverage the use of protected areas to halt the loss of global biodiversity. Target 11 recommends that ecologically representative portions (10%) of important coastal and marine areas be set aside within MPAs. Despite global progress in attaining the 10% target, few areas are set aside with consideration of ecological representation (area and diversity of features) as a conservation goal. Using publicly available datasets of marine geomorphic features and benthic habitats, we assessed the relative representativeness of features, by assessing feature coverage and diversity, within existing protected areas of both Large Marine Ecosystem (LMEs) and Exclusive Economic Zones (EEZs). Only 18 of the 66 LMEs contained greater than 10% of their marine geomorphic features and benthic habitats within MPAs. The Caribbean, Pacific Central, Mediterranean and Canary Current LMEs were identified as areas that protected the most diversity, while the geomorphically diverse Arctic Ocean had the least area of features within MPAs. Less than one quarter of EEZs (46 out of 230) had more than 10% of their geomorphic features and benthic habitats within MPAs. The coral triangle and other warm water reef areas are clear priorities for conservation, exhibiting high diversity of geomorphic features and benthic habitats, yet, most LMEs and EEZs in these areas fail to achieve representativeness or 10% feature coverage. Australia, New Zealand and the United States and areas in Europe and the South Pacific achieve relative representativeness scoring highly in coverage and diversity of features protected. Assessing the coverage and diversity of protected features within EEZs and LMEs can assist nation states and ecosystem management regions to better assess representativeness in achieving the 2020 Aichi targets. Highlights: Less than ¼ of all EEZs had more than 10% of their features and habitats within MPAs. Only sixteen LMEs had more than 10% of seafloor features and habitats within MPAs. Thirty-nine EEZs had no seafloor geomorphic feature coverage within their MPAs. Increasing MPA coverage does not always increase feature representativeness.